Farmers' perceptions of extension agents' professional qualities affecting service delivery in Thulamela Municipality, Limpopo Province - Mudzanani, Funzani Joyce (My University, 2019)
This study investigated farmers’ views on public extension agents’ accountability to farmers since the introduction of the farmers’ green book, improvement in agents’ professional qualities following capacity training and their technical competence following qualification upgrade since the implementation of the Extension Recovery Plan (ERP) in 2008/2009. The study was conducted among 80 farmers in Thulamela Municipality of Limpopo where farmers have been supplied with the farmers’ ‘green book’ by the Limpopo Department of Agriculture (LDoA) and where agents of LDARD have undergone qualifications’ upgrades and capacity training in competency areas since ERP implementation. The findings in this study suggest that the introduction of the farFmers’ green book improves AEs accountability to farmers. There is also evidence from the study that seems to suggest that farmers believe EAs farm management knowledge of crop and animal production has also improved. Furthermore, farmers believe that EAs now demonstrate more professional conduct in agricultural extension service delivery. The introduction of the ERP seems to be making a positive contribution to improve the effectiveness of the public agricultural extension in South Africa. Flowing from the findings of this study it is appropriate to recommend that more farmers’ green books should be made available to farmers, more funds be available to encourage more extension agents with diploma qualifications to enrol in tertiary institutions to upgrade their qualifications to at least a bachelor’s degree and more capacity training in the areas identified in the Norms and Standards (2005) should take place and made mandatory for agents to attend. This should, perhaps, be linked to promotions to encourage agents to attend. Keywords: Norms and Standards, farmers’ green book, ERP, accountability, capacity training, qualification, upgrade.
Thesis (M. Sc. Agricultural Management (Agricultural Extension)) -- University of Limpopo, 2019
Keywords: Norms and Standards; Farmers’ green book; ERP; Accountability; Educational accountability -- South Africa; Agriculture, Cooperative; County agricultural agents -- South Africa.